FORMAL METHODS OF EXPERT ESTIMATIONS - Tea Ya. Danelyan (Статистика и экономика, 2016)
This article series discusses formal methods of expert assessments. Usingthe Delphi method helps to formalize theprocedures for the collection, compilationand analysis of the views of specialists inorder to convert them into a form most convenient for making an informed decision.